2019
DOI: 10.1016/j.ajhg.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program

Abstract: Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…However, genetics do not fully explain HbA 1c differences among African American people ( 44 ), because increases in HbA 1c may be mediated by social determinants of health (eg, chronic financial strain as seen in study 3) or chronic inflammation (sIL-6R) ( 28 , 45 ). Additionally, G6PD variant or deficiency is often correlated with lower HbA 1c values in various populations ( 40 ), especially in African American people and African people because of its higher prevalence in these groups ( 14 , 46 , 47 ). Similarly, the sickle cell trait is associated with lower HbA 1c values in African descent populations ( 21 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, genetics do not fully explain HbA 1c differences among African American people ( 44 ), because increases in HbA 1c may be mediated by social determinants of health (eg, chronic financial strain as seen in study 3) or chronic inflammation (sIL-6R) ( 28 , 45 ). Additionally, G6PD variant or deficiency is often correlated with lower HbA 1c values in various populations ( 40 ), especially in African American people and African people because of its higher prevalence in these groups ( 14 , 46 , 47 ). Similarly, the sickle cell trait is associated with lower HbA 1c values in African descent populations ( 21 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously suggested that HbA1c-associated variants appear to exert their effects on HbA1c levels through both glycaemic and non-glycaemic pathways 7,45 Classification of loci into these pathways can have important implications for T2D diagnostic accuracy 7,46 . To further elucidate the biology of HbA1c-associated variants, we took advantage of prior association results for other glycaemic, RBC, and iron traits, and used a fuzzy clustering approach to classify variants into their most likely mode of action ( Methods, Supplementary note ).…”
Section: Resultsmentioning
confidence: 99%
“…Future updates for MPM will be focused on providing more complete, high-quality human interactome (including protein-DNA/RNA interactions as well), functional sites, and proteogenomics data from CPTAC. We will integrate more human genome sequencing data, including Trans-Omics for Precision Medicine (TOPMed) Program [ 63 ], Alzheimer’s Disease Sequencing Project (ADSP) [ 64 ], and International Cancer Genome Consortium (ICGC) [ 65 ], to improve utilities of MPM by adding more personalized genome analyses.…”
Section: Limitation and Future Directionsmentioning
confidence: 99%